Risk, behavior asymmetries and willingness to adopt co-produced climate-informed advisory for pastoralists and agro-pastoralists in Senegal - Houessionon, Prosper; Chan, Derek; Worou, Nadine; Wane, Abdrahmane; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This study aims to develop tailored and context specific climate advisories that engage community perceptions, local knowledge and livelihood patterns for climate risk and uncertainty management in livestock farming.